Liderazgo de los jóvenes universitarios en tiempos de COVID-19, aportes desde una experiencia socioformativa. - Misas Hernández , Jorge; López Rodríguez del Rey, María Magdalena; Fernández Bereau , Vanesa Bárbara (Revista Perspectiva Científica, 2025)
Leadership training is an implicit task in the mandate of universities. Curriculum and extracurricular activities ensure influences that guide and condition the development of leadership skills and abilities. However, the participation of young university students in confronting the COVID-19 pandemic became an unprecedented experience in the empowerment of youth leadership. The impact of this experience a few years later was the focus of the author’s reflection. The problem was defined as: What formative impact did the participation of young university students have during the experience of confronting COVID-19? The objective was to identify the formative impact of the participation of young university students during the experience of confronting COVID-19. The systematization of experiences was chosen as a methodology that facilitates the socialization and discussion of ideas. In the process, the meanings and senses of this experience emerged, as well as the aspects that should be considered as a cornerstone for new socio-formative experiences. The results support leadership development based on the comprehensive learning experience, which resulted from their participation in the efforts to combat the pandemic, particularly in collaborative work to solve social problems, health promotion, social assistance, and food production.